Surgically-Treated Locoregionally Advanced Hypopharyngeal Cancer: Outcomes - Rodrigues, Jorge; Breda, Eduardo; Monteiro, Eurico (International Archives of Otorhinolaryngology, 2018)
Introduction Hypopharyngeal tumors are head and neck malignancies associated with a great mortality rate, and the treatment of advanced lesions constitutes a challenging problem. Pharyngolaryngectomy continues to be the gold standard treatment modality for locally-advanced diseases, and it is currently used as the primary treatment or in cases of relapse after an organ preservation strategy.Objective This study aims to compare the survival rates of patients with advanced hypopharyngeal tumors treated with pharyngolaryngectomy as a primary or salvage option, and identify possible prognostic factors.Methods All patients with advanced hypopharyngeal squamous cell carcinomas who performed pharyngolaryngectomy between 2007 and 2014 were reviewed retrospectively.Results A total of 87 patients fulfilled the aforementioned criteria, and the sample had a mean age of 57.2 years and a male predominance of 43:1. The tumors were located in the pyriform sinus walls (81 tumors), in the posterior pharyngeal wall (4 tumors) and in the postcricoid region (2 tumors). A total of 60 patients underwent surgery as the primary treatment option, and 27 were submitted to salvage pharyngolaryngectomy after a previous treatment with chemoradiotherapy or radiotherapy. The 5-year overall survival was of 25.9%, the 5-year disease-free survival was of 24.2%, and the disease-specific survival was of 29.5%.Conclusion The patients treated with pharyngolaryngectomy as the primary option revealed a better 5-year-disease free survival than the patients who underwent the salvage surgery (35.8% versus 11.7% respectively; p < 0.05). The histopathological criteria of capsular rupture of the lymph nodes (30.1% versus 19.8% respectively for the primary and salvage groups; p < 0.05) and vascular invasion (30.5% versus 22.5% respectively; p < 0.05) reduced the 5-year disease-free survival. Pharyngolaryngectomy as the primary intent revealed a lower local recurrence rate than the salvage surgery (40.6% versus 83.3% respectively; p < 0.05).
Keywords: laryngeal cancer; laryngectomy; hypopharyngeal cancer; laryngeal neoplasms; hypopharyngeal neoplasms